On the way of DNA Metallization: Principle, methods, and recent applications - Albarqouni, Yasin; M. Ali, Gomaa A.; Ab. Rahim, Mohd-Hairul; Kwok Feng, Chong (ISSR Publishing, 2020)
Recent years have witnessed tremendous coherent growth with great achievements on the DNA metallization approach, from its simple synthesis techniques to the present construction of wide range nanostructures for versatile applications in different disciplines, including chemical catalysis, environmental, or bio-sensing, and biomedical engineering. Hence, our aim here is to provide as much as possible a coherent review, leading to illustrate the research achievements on DNA metallization since revealing the DNA metal back in 1998. A systematic and comprehensive illustration starts with DNA fundamental knowledge with a brief discussion on the outstanding chemistry enrichment that denotes DNA the capability to tune metal’s growth on its helix, the next section is presenting various reported construction methods and techniques of the grown metals. Afterward, the discussion is elaborated on the applications of DNA-metal nanomaterials in different fields. For that, the present work could be considered of great value to provides promotion for future works of DNA metallization with enjoying researchers from different fields.